Ambiente visual para el aprendizaje de los conceptos básicos asociados a la recurrencia (2017)
This project has been developedinorder to show students the importance of visualizing patterns and how recurrence contributes to the solutionofproblemsof the algorithmic nature, since not all educational entities teach concepts associated with recurrence and Students have little knowledge about this subject. To change this teaching paradigm, this article develops a visual environment where students can interact with a recurrence exercises basic series. The environment works ​ graphically, interactively and dynamically in orderto help in the development of skills in this topic